THE EFFECT OF FIRM SIZE, FIRM OPERATING COMPLEXITY, PROFITABILITY, AND SOLVABILITY, ON AUDIT DELAY WITH PUBLIC ACCOUNTING FIRM SIZE AS MODERATING VARIABLES IN MANUFACTURING COMPANIES IN INDONESIA STOCK EXCHANGE - Marbun, Irsan Munawir (Asosiasi Dosen Akuntansi Indonesia, 2019)
the objective of the study is to analyse the effect of firm size, firm operating complexity, profitability and solvability of audit delay with public accounting firm (PAF) size as a moderating variable in manufacturing companies on the Indonesia Stock Exchange. This type of research is causal associative research. The research method uses secondary data collection techniques. The population in this study includes manufacturing companies listed on the Indonesia Stock Exchange from 2009 to 2018. The sampling method used in this study is purposive sampling. Data were processed using panel data regression analysis. The results showed that firm size had a negative and significant effect on audit delay. The complexity of the firm operations has a positive and not significant effect on audit delay. Profitability has a negative and significant effect on audit delay. Solvability has a positive and not significant effect on audit delay. PAF size is a moderating variable for the relationship between firm size, complexity of firm operations and solvability to audit delay. However, PAF size is not a moderating variable for the relationship between profitability and audit delay.